Challenges in the Development of Drug Delivery Systems Based on Small Extracellular Vesicles for Therapy of Brain Diseases - Loch-Neckel, Gecioni; Matos, Ana Teresa; Vaz, Ana Rita; Brites, Dora (Frontiers in Pharmacology, 2022)
Small extracellular vesicles (sEVs) have 30-200 nm diameter size and may act as carriers of different cargoes, depending on the cell of origin or on the physiological/pathological condition. As endogenous nanovesicles, sEVs are important in intercellular communication and have many of the desirable features of an ideal drug delivery system. sEVs are naturally biocompatible, with superior targeting capability, safety profile, nanometric size, and can be loaded with both lipophilic and hydrophilic agents. Because of their biochemical and physical properties, sEVs are considered a promising strategy over other delivery vehicles in the central nervous system (CNS) since they freely cross the blood-brain barrier and they can be directed to specific nerve cells, potentiating a more precise targeting of their cargo. In addition, sEVs remain stable in the peripheral circulation, making them attractive nanocarrier systems to promote neuroregeneration. This review focuses on the recent progress in methods for manufacturing, isolating and engineering sEVs that can be used as a therapeutic strategy to overcome neurodegeneration associated with pathologies of the CNS, with particular emphasis on Alzheimer’s, Parkinson’s and amyotrophic lateral sclerosis diseases, as well as on brain tumors.